Centromere evolution and CpG methylation during vertebrate speciation. Issue 1 (December 2017) - Ichikawa, Kazuki; Tomioka, Shingo; Suzuki, Yuta; Nakamura, Ryohei; Doi, Koichiro; Yoshimura, Jun; Kumagai, Masahiko; Inoue, Yusuke; Uchida, Yui; Irie, Naoki; Takeda, Hiroyuki; Morishita, Shinich
Abstract Centromeres and large-scale structural variants evolve and contribute to genome diversity during vertebrate speciation. Here, we perform de novo long-read genome assembly of three inbred medaka strains that are derived from geographically isolated subpopulations and undergo speciation. Using single-molecule real-time (SMRT) sequencing, we obtain three chromosome-mapped genomes of length ~734, ~678, and ~744Mbp with a resource of twenty-two centromeric regions of length 20–345kbp. Centromeres are positionally conserved among the three strains and even between four pairs of chromosomes that were duplicated by the teleost-specific whole-genome duplication 320–350 million years ago. The centromeres do not all evolve at a similar pace; rather, centromeric monomers in non-acrocentric chromosomes evolve significantly faster than those in acrocentric chromosomes. Using methylation sensitive SMRT reads, we uncover centromeres are mostly hypermethylated but have hypomethylated sub-regions that acquire unique sequence compositions independently. These findings reveal the potential of non-acrocentric centromere evolution to contribute to speciation. Centromeres and large-scale structural variants evolve and contribute to genome diversity during vertebrate speciation. Here Ichikawa et al perform de novo long-read genome assembly of three inbred medaka strains, and report long-range structure of centromeres and their methylation as well as correlation of structural variants with differential gene expression.